UNSUR-UNSUR PENGHIDUP DAN TEKNIK PENERAPANNYA DALAM PROSES ANIMASI DAN PENGEKSPRESIAN PADUAN SUARA - Rizky Jonathan Rantung; Perry Rumengan; Franklin Dumais (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
The purpose of this study is to find out how to turn on a choir using Qualitative methods with Approaches to Musicology, Psychology, and Communication. Data collection is done through library research, literature collecting, and reading sources to obtain basic knowledge about the object of research. These sources can be in the form of books, journals, articles, theses, and interviews. Choir is a type of musical composition with human voice instruments, which in the process of making the composition, the composer takes into account the color of the voice, the ability to reach both high and low speed, power volume and balance, and blending, as well as Dixie clarity. The main problem at this time is there are still many conductors and even choir trainers who do not understand the elements of life and how to apply/apply animation and expression techniques in the choir because there are still many trainers and even conductors who only rely on Youtube and do not yet exist scientific writing on the Living Elements and their application techniques in the process of Animation and Choir Expression. Therefore, I hope this article can help the coaches and even the choir conductors, especially those in North Sulawesi